Understanding the outsourcing decision in South Africa with regard to ICT - K. A. Johnston; T. Abader; S. Brey; A. Stander (South African Journal of Business Management, 2009)
Information and Communication Technology (ICT) outsourcing is a strategic initiative adopted by many organisations across all industries. Outsourcing is seen as a means for organisations to concentrate and improve their core business functions. Despite the vastly dynamic environment businesses operate in, few global studies have uncovered the factors influencing outsourcing decisions, thus the need for this paper. The research was performed using a number of statistical tests and descriptive analysis methods to explore the literature and to determine the current status of South Africa's ICT outsourcing market. Key findings reveal that cost is the most influential factor when deciding whether to outsource or not, irrespective of organisations size or type. Other important factors include concentrating on core-functions, and the availability of in-house expertise. The form of outsourcing used is not affected by the size of the organisation. Application Service Providers (ASP) is the most common form, followed by co-sourcing.
Keywords: 650